Spindle cell hemangioma of the lung: An unusual presentation. Issue 11 (17th October 2022) - Hamdi, Mariem; Braham, Emna; Louhaichi, Sabrine; Hamdi, Besma; Abdennadher, Mahdi; Ammar, Jamel; El Mezni, Faouzi; Marghli, Adel; Hamzaoui, Agnès
Abstract: Spindle cell hemangioma (SCH) is a benign vascular tumour, first identified by Weiss and Enzinger in 1986. Habitually, the SCH affects almost exclusively the dermis and subcutaneous tissues of distal extremities. So far, only 2 cases have been described in the lung. We describe herein the third case of SCH occurring in the lung in a 47 year‐old woman. The patient was successfully treated by right lower lobectomy. The histopathological and immunohistochemistry examination of the excised tumour leads to the definitive diagnosis. Our case is instructive by its different clinical and radiological presentation compared to the previous two cases. Abstract : SCHs are benign vascular tumor that occurs in young adults and typically arises in the subcutis of the distal extremities, particularly the hand. So far only two cases of pulmonary SCH were reported in the literature. Our case is instructive by its different clinical (hemoptysis) and radiological presentation (cavitary lesion) compared to the previous two cases.